Direct costs of first‐generation protease inhibitors for the treatment of genotype 1 chronic hepatitis C viral infection. Issue 12 (25th May 2015) - Sethi, N.; Tapper, E. B.; Vong, A.; Sethi, S.; Rourke, M.; Afdhal, N. H.
Summary To evaluate the cost‐effectiveness of Hepatitis C therapy, robust real‐world data are needed to understand the costs and benefits of treatment alternatives. The objective of this study was to evaluate the true direct cost of treatment in an unselected sequential population of patients treated at a tertiary care centre for hepatitis C virus genotype 1. A total of 200 consecutive patients were treated with interferon, ribavirin and a first‐generation direct‐acting antiviral agent (DAA) between 2011 and 2013. A total of 41% had cirrhosis, 31% were prior relapsers, and 41% were prior partial or null responders. Costs used were wholesale acquisition cost prices for medications, average hospital costs per day for each diagnosis code based on US inpatient hospital charges. All costs were adjusted to 2013 dollars. Sustained virologic response (SVR) was achieved in 97 patients (48.5%). A total of 14% experienced relapse, 19% breakthrough or nonresponse, and 18.5% discontinued secondary to side effects. Twenty per cent of patients had at least one hospitalization attributable to a complication of therapy. Thirty‐seven per cent of patients required erythropoietin‐stimulating agents, 16% received filgastrim, and 15% needed a red blood cell transfusion. The mean overall cost of treatment was 83 851 per patient. The cost per SVR was 172 889; 266 670 for patients with cirrhosis. The costs per SVR after treatment with first‐generation DAAs are dependent on the stage of disease and therapy side effects. These real‐world costs significantly exceed those described in prior cost‐effectiveness assessments and should be used instead for future studies.